Determination of Optimum Alkali Reagent for Cocoa Powder Alkalization: Effects on Physico-chemical, Functional and Technological Characteristics - Demirci, Sultan; Elmaci, Ceren; Atalar, Ilyas; Toker, Omer Said; Palabiyik, Ibrahim; Konar, Nevzat (SPRINGER, 2025)
In this study, alkalized cocoa powders were obtained by optimization study with the Mixture Design, which included the use of the main alkali salts (NaOH, KOH and K2CO3). The effects of the alkali salt(s) used on the antioxidant activity (DPPH and ABTS methods), total phenolic compounds, particle size distribution, physicochemical (pH, moisture content, water activity, total ash amount, color) and volatile component profiles of samples were investigated. Significant models with high R-2 values (0.8297-0.9983) were determined for all main alkalization indicators (a*/b*, pH, and TrMP/TMP), color characteristics, Sauter mean (D3:2), bulk and tapped density (p < 0.05). It has been determined that classification based only on pH and color properties in alkalization may cause disadvantages in terms of polyphenol content and aroma profile, which are among the main motivation factors for consumption of cocoa-based products. In addition, the effects of alkalis on stability and technological properties should also be taken into consideration for this process.
Keywords: Alkalization; Cocoa; Powder; Chocolate; INLET TEMPERATURE; COLOR; POLYPHENOLS; QUALITY; MILK; DARK; Food Science & Technology